The Effect of Applying the Gagnon and Collay Learning Model in Biology Learning on Student Learning Outcomes at SMA Negeri 13 Bone - suryani, Suryani; Wahyuni, Sri; Asmah, Sitti (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
Students have difficulty understanding biology learning material, for this reason students need to be directed to understand biology learning concepts. This research aims to determine the effect of applying the Gagnon and Collay learning model in biology learning on student learning outcomes at SMA Negeri 13 Bone. The research used is a quantitative method with a Pre-Experimental Design type. where this research uses one class, namely the experimental class, at the beginning of the learning a pretest (initial test) will be given and at the end of the learning a posttest (final test) will be given. The research results obtained by the author are that the use of the Gagnon and Collay learning model can influence student learning outcomes at SMA Negeri 13 Bone. The average student pre-test score was 41.8 and the average post-test score was 85.4. Where using the Gagnon and Collay learning model can help students become more active in the learning process, apart from that students can also develop their creative patterns because they must be able to show their learning results or work, as well as help students to collaborate with members of their respective groups. This research can be input for teachers as a model that can help students improve their learning outcomes.